TAREKAT KHALAWATIAH SAMMAN (Studi tentang Penyebaran dan Ajarannya di Masyarakat Masamba Kabupaten Luwu Utara Sulawesi Selatan) - Nurlidiawati, Nurlidiawati (RIHLAH, 2013)
Mystical path avoiding what is prohibited and what it can lead to sin, It noticed what is possible and what is not, it is also doing what is useful to do and what is sinful when done. The ability of a person is under the guidance of a leader (sheikh) with a specific purpose.